Intramuscular Mass in a Proximal Injury of the Rectus Femoris Muscle - Hematoma or Neoplasia? - Amorim,Edgar (2024)
Abstract An organized hematoma reflects a late complication of muscle injuries. It is important to note that the appearance of a muscular hematoma on ultrasound may be similar to other conditions, such as a tumor (e.g. sarcoma), so further evaluation may be necessary to obtain an accurate diagnosis.